Smokers' perception, attitudes towards smoking cessation when visiting a smoker physician - Abdulaziz A Alodhayani; Abdulelah I Alhussain; Fahad M Alshughaithry; Saad A Aloqile; Saad A Alowaimer; Khaled A Showail; Salem Mohammed Basalem (Wolters Kluwer Medknow Publications, 2021)
Background: Smoking is one of the leading risk factors that raised mortalities and morbidities significantly. Smoking cessations programs were implemented to reduce the number of smokers. Many factors may influence the smoking cessation including factors related to the treating physician. Objective: To determine smokers' perception and attitude towards smoking cessation when knowing the physician is a smoker. Methods: This was an observational cross-sectional survey study that has been conducted among smokers' patients at King Khalid University Hospital in Riyadh, the estimated sample size was 200 participants. Results: The participants who saw a smoking physician were 90% and 8.8% of them were supported by physicians to quit smoking. The remaining 10% participants reported that they did not see a smoking physician and 15.8% of them were supported by physicians to quit smoking. There was significant correlation between attitude toward smoking cessation and the smoking status and the highest score was found among current smokers and lowest score among ex-smokers (P-value= 0.012). Moreover, the score was highest among those who have history of failed attempt to quit smoking. Lastly, there was no statistically significant difference in scores based on perception and attitude towards smoking cessations when knowing the physician is a smoker. Conclusion: The present study assessed the level of perception and attitude among smokers and the results suggest a different impact of smoker physicians and compared it according to characteristics of smoking. Also, this study showed variations in the behaviors of smoking and cessation, smoking-related barriers that prevent patients from stopping smoking based on physician smoking status.